Linear and nonlinear optical properties of carbon dot gel glasses - Low, Pei Jiang (2015)
Carbon dots are an emerging type of nano-sized photoluminescent material which has many attractive characteristics. Recently, carbon dots have been incorporated into gel glass matrices in high concentration via sol-gel fabrication method, called the organosilane functionalised carbon dot gel glasses (SiCD-gel), making it a potentially versatile optical material. It is thus interesting to study the optical properties of this new material. In this study, the linear and nonlinear optical properties of the SiCD-gel in different doping concentration are investigated. The linear absorption is found to red shift at high doping concentration of SiCD. The photoluminescence peak shows excitation wavelength dependent behaviour for the low concentration sample. The samples are found to have positive third order nonlinear absorption and the coefficients are quantified for the first time. The cause of the nonlinear absorption is identified to be due to two-photon absorption. The experiments also seem to suggest that the carbon dots near the surface of the high concentration sample are green photoluminescent and blue in the centre.